(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Disaster preparedness is essential in developing community resilience among future educators; however, existing studies indicate a gap between students’ disaster awareness, participation in Disaster Risk Reduction and Management (DRRM) activities, disaster preparedness, and their engagement in emergency management practices. This study examined the influence of disaster awareness, participation in DRRM activities, and disaster preparedness on student engagement in emergency management practices among education students. Guided by the Protection Motivation Theory (Rogers, 1975), the study employed a descriptive-correlational research design involving 141 students selected through stratified random sampling. Data were collected using a validated survey questionnaire measuring the variables of disaster awareness, participation in DRRM activities, disaster preparedness, and student engagement in emergency management practices. Descriptive analysis revealed generally high levels across the measured variables. Multiple regression analysis indicated that disaster awareness, participation in DRRM activities, and disaster preparedness significantly influenced student engagement in emergency management practices, with participation emerging as the strongest predictor. The findings highlight that while awareness provides foundational knowledge, active participation in DRRM initiatives and practical preparedness activities play a stronger role in enhancing students’ readiness and engagement in emergency management practices. These results underscore the importance of strengthening experiential and participatory DRRM initiatives within teacher education programs to further enhance students’ preparedness and engagement in emergency management practices.